LEARNERS’ STRATEGIES IN IMPROVING THEIR VOCABULARY 64 MASTERY - Safitri, Marita (Universitas Bandar Lampung, 2018)
Learners frequently do not care about the strategies they use to improve their vocabulary mastery. On the other hand, a strategy is important in learning and increasing for both vocabulary and knowledge. Therefore, the objective of this research is to find out the strategies that the students adopt to improve their vocabulary mastery. A survey method was used in this research. A questionnaire was used based on Vocabulary Learning Strategy Questionnaires (VLSQ) that is designed by Schmitt’s Taxonomy. It consisted of 25 items. Data were analyzed by using descriptive analysis. The results showed that the students in this survey are medium strategy users and the metacognitive strategy is the strategy the students of Academy of Foreign Language of Sinema Yogyakarta mostly adopt to improve their vocabulary mastery. It is followed by memory, determination, social (discovery), cognitive and the least is social (consolidation). In the context of English as Foreign Language students, it is suggested to the students and other readers to balance the five strategies in applying them both in learning and in improving their vocabulary mastery.